Analysis of the Implementation of the DSN-MUI Fatwa and Maqashid Sharia in Sharia Hotels: A Study at the Lor In Sharia Solo Hotel - Adinugraha, Hendri Hermawan; Tamamudin, Tamamudin; Abidin, Rohmad; Firdaus, Muhammad Izzat; Syakirunni'am, Luqman (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: The development of Sharia hotel studies goes hand in hand with research on halal tourism. Sharia hotels are the latest trend in the halal industry. The concept and its implementation concerning the conformity of sharia principles has become a current research problem. This study will analyze the application of DSN-MUI fatwas and maqashid sharia at the Lor In Sharia Solo Hotel. Research Methods: The methodology used in this research is qualitative, using a field research approach. The object of this research is the management of the Lor In Sharia Solo Hotel with the DSN-MUI fatwa approach and Maqashid sharia. The purposive sampling technique determined the data source of this research. The informants in this study are managers, staff, employees, and visitors or consumers of the Lor In Sharia Solo Hotel. Research data has been collected through observation techniques, interviews, and documentation. Analysis of research data has used qualitative techniques, which include data reduction, data presentation, and concluding verification. Results: The empirical findings of this study have shown that the Lor In Sharia Solo Hotel in Solo is following the parameter indicators contained in the DSN-MUI fatwas and maqashid sharia. Conclusion: Based on the results and research findings in this article, it can be concluded that the form implementation of the two instruments in the Lor In Sharia Solo Hotel has a positive impact on the development of Islamic economic practices in Solo.